Pengaruh penyuluhan manfaat sayur dan buah terhadap asupan zat gizi remaja obesitas siswa/siswi SLTP di Kota Palembang - Yulianto Yulianto; Hamam Hadi; R Dwi Budiningsari (Jurnal Gizi Klinik Indonesia, 2007)
Background: Indonesia is a tropical country rich in various vegetables and fruits which are necessary for health because they contain lots of vitamins, minerals and fibers. However, Indonesian children and teenagers do not often pay attention to balanced nutrition, particularly vegetables and fruits. They even tend to choose fast food which may lead to occurrence of obesity. Prevalence of obesity among teenagers becomes an important issue because it persists to adulthood. Impact of obesity is a threat to public health and needs serious attention. Considering the important role of vegetables and fruits for health especially among obese teenagers, awareness on the necessity of consuming those needs to be made and built through nutrition counseling.Objective: The objective of the study was to identify the effects of counseling on the advantages of vegetables and fruits consumption to nutrient intake (energy, protein, fat, carbohydrate and fiber) among obese teenage students of junior high school at Palembang Municipality.Method: The study was quantitative with quasi experimental design. Subject of the study were obese teenage students of junior high school at Palembang Municipality aged 12 – 15 years old. There were 72 respondents of intervention group and 72 respondents of control group. Samples were taken using non random sampling technique. T-test was used to find out effects of counseling to consumption of vegetables and fruits and nutrient intake before and after intervention.Result: Delta average value of fruit consumption and nutrient intake (energy, fat, carbohydrate, and fiber) based on t-test analysis showed significant difference in both groups with p<0.05. Meanwhile, delta average value of vegetable consumption and nutrient intake (protein) did not show significant relationship (p>0.05).Conclusion: Counseling on the advantages of vegetables and fruits affect consumption of fruits and nutrient intake (energy, fat, carbohydrate and fiber).